2012
DOI: 10.2140/gt.2012.16.555
|View full text |Cite
|
Sign up to set email alerts
|

Tree homology and a conjecture of Levine

Abstract: In his study of the group of homology cylinders, J Levine [23] made the conjecture that a certain group homomorphism Á 0 W T ! D 0 is an isomorphism. Both T and D 0 are defined combinatorially using trivalent trees and have strong connections to a variety of topological settings, including the mapping class group, homology cylinders, finite type invariants, Whitney tower intersection theory and the homology of Out.F n /. In this paper, we confirm Levine's conjecture by applying discrete Morse theory to certai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(63 citation statements)
references
References 26 publications
2
61
0
Order By: Relevance
“…As explained in section 5 (Theorem 5.5), this result follows from the relationship between the Whitney tower intersection invariant τ and Milnor invariants [11,38], together with our proof in [12] of a combinatorial conjecture of J. Levine [29], which also implies that T 2k is a free abelian group of known rank [12, Thm.1.5].…”
Section: Ihxmentioning
confidence: 66%
See 1 more Smart Citation
“…As explained in section 5 (Theorem 5.5), this result follows from the relationship between the Whitney tower intersection invariant τ and Milnor invariants [11,38], together with our proof in [12] of a combinatorial conjecture of J. Levine [29], which also implies that T 2k is a free abelian group of known rank [12, Thm.1.5].…”
Section: Ihxmentioning
confidence: 66%
“…As a first step towards our goal of describing a classification of this filtration and the associated W n , we recall (e.g. from [9,12,30,38]) a combinatorially defined group which is a natural target for the intersection invariant associated to the obstruction theory for Whitney towers.…”
Section: The Whitney Tower Filtration Of Classical Linksmentioning
confidence: 99%
“…Conversely, there is an epimorphism R n : T n → W n , called the realization map, such that R n (φ) is the class of a link bounding an order n framed Whitney tower T in D 4 withτ n (T ) = φ. For even n, they showed that T 2ℓ ∼ = Z M(m,n) where m is the number of link components, using their proof of the Levine conjecture [CST12a,CST12c]. (Recall that M(m, n) is the rank of D n ; see Remark 3.2.)…”
Section: Some Results From the Integral Framed Theorymentioning
confidence: 99%
“…In Theorem 3.1 (2), µ n denotes the total Milnor invariant of order n, and η n denotes the summation map which was formulated in [Lev01,Lev02] and used extensively in [CST12c,CST14,CST12a]. We will review their definitions in Section 3.1.…”
Section: Milnor Invariants and Rational Whitney Towersmentioning
confidence: 99%
See 1 more Smart Citation